Beyond genres : Melusine's case - Charnay, Bochra (Ondina - Ondine, 2020)
This article explores a corpus built around the Melusian cycle, composed of the novel by Jean d'Arras, several versions of type 425 tale and the Poitevin legend. It develops a reflection on the concept of gender in the context of the university teaching of Youth literature. It puts forward that the texts tackled seperately, set out invariants linking one another to a generic category identifiable by the recipient according to his or her horizon of expectation. On the other hand, these very texts confronting one another, create a scrambling between their boundaries which appear as being porous, and therefore it becomes difficult to class them in a single and well-defined genre. That's why the article emphasizes the limits of the concept of genre according to its classificatory and static effect and it replaces it by the principle of genericity put forward by Jean-Michel Adam and Ute Heidmann ; the latter being considered as being more flexible and more dynamic, highlights the richness of the interactions between the different discourses and underlines the intergenic link which originates in their formation.